Evaluation of the maternal photoperiodic effect as a storage method on Trichogramma nerudai - Viscarret, Mariana Mabel; Cagnotti, Cynthia Lorena; Lopez, Silvia Noemi (Department of Agroenvironmental Sciences and Technologies, Università di Bologna, 2024)
Maternal photoperiodic effect on Trichogramma nerudai Pintureau et Gerding (Hymenoptera Trichogrammatidae) was evaluated to test its possible exploitation to store the parasitoid. Freshly parasitized eggs of Sitotroga cerealella (Olivier) (Lepidoptera Gelechiidae) were randomly assigned to one of the following light (L)/dark (D) cycles (hours) (treatments): 3L:21D, 6L:18D, 9L:15D and 12L:12D. This was the maternal generation (P1). Once the P1 emerged, they were exposed for 24 hours to fresh eggs of S. cerealella. The resulting parasitized eggs (F1 generation) were maintained under a moderately low temperature (11 ± 2 °C) and complete darkness. All the variables registered on the F1 were affected by light/dark cycles. A longer time of emergence was registered for treatments 3L:21D and 12L:12D (94 and 92 days, respectively). The lowest times of emergence, were for 6L:18D and 9L:15D treatments (68 and 55 days, respectively). Treatment 3L:21D (80.20 ± 2.46%) presented the highest value of emergence following for 12L:12D (69.85 ± 3.10%), 6L:18D (62.70 ± 2.87%) and finally 9L:15D (25.90 ± 3.25%). About the female proportion, treatment 3L: 21D had the highest value (0.61 ± 0.02), followed by treatment 12L:12D (0.51 ± 0.02). The female proportion was similar for treatments 9L:15D (0.41 ± 0.03), and 6L:18D (0.43 ± 0.02). The non-emerged and dissected material showed a high proportion of prepupal diapausing stage on 12L:12D treatment. However, other treatments presented a high proportion of pupal and adult non-emerged showing other quiescent stages for this parasitoid. Treatment 3L:21D on P1 generation keeping the F1 on a relative low temperature showed the best combination to obtain ca 90 days of storage, with high values of adult emergence and female parasitoid proportion.